Green Human Resource Management Practice in Bangladesh Readymade Garments Industries - T. N. Sonia Azad; Jannatul Mawa Moon; GM Faysal; Md. Tanjim Hossain (Journal of Social Science, 2022)
Green Human Resource management (GHRM) is not commonly practiced in the ready-Made Garments (RMG) sectors in Bangladesh. Only a few factories practiced the GHRM and they achieved many international awards as well as developed their business rapidly. RMG sector in Bangladesh could benefit from implementing GHRM and establishing sustainable development. This is the quantitative analysis and random sampling methods used to select the garments factories and representatives. Ten garments industries were randomly selected . Five managers were selected from different departments in each garments factory. They informed that the many obstacles to GHRM practices in the RMG sector in Bangladesh. The researcher found some major obstacles like organizational support, inadequate turnover of managerial interests, high costs of practice, and employee turnover. It is possible to successfully implement the GHRM practice in Bangladesh's RMG industry by implementing tight regulations and rules, supervision, training programs, incentives, and mandatory courses in the education system. The suggestion of this research paves the way for improved GHRM methods. The research outcomes would increase GHRM practice in the RMG sectors and may be utilized for innovative contributions to Bangladesh's RMG businesses.